Formation of metal-free binaries: impact of H2 line cooling and CIE cooling - Riaz, Rafeel; Schleicher, D. R. G.; Bovino, S.; Vanaverbeke, S.; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2023)
During primordial star formation, the main cooling channel is provided by H2 and super-molecules, such as H2 or H2, at sufficiently high densities. When the latter form at nH≥1014 cm−3, collision-induced emission (CIE) provides efficient gas cooling. We investigate how CIE cooling affects the formation of metal-free binaries comparing simulations with and without this process. Irrespective of the cooling mechanism, we find a typical protostellar mass range between 0.01 and 100 M⊙. However, models with only H2 line cooling produce a greater number of low-mass protostars that exhibit stronger variations in their radial velocities than the high-mass protostars. Similarly, in models with both H2 cooling and CIE cooling, significant variations in the radial velocities are found for protostars in the intermediate-mass range. The initial number of fragments Nmax decreases with increasing strength of turbulence. Cooling via super-molecules lets the most massive protobinaries (MMPBs) efficiently accrete mass. The maximum mass accretion rate M˙max for the MMPBs is more than an order of magnitude higher in the presence of CIE cooling than for pure H2 line cooling. As a result, compact binaries with a semimajor axis as small as 3.57 au may form through the H2– H2 cooling channel. Our results indicate that, in addition to the MMPBs, most population III (Pop. III) binaries should be in eccentric i.e. non-circular orbits. This provides an important connection to the eccentric binaries reported in previous studies, which were found to exhibit rich temporal accretion signals during their evolution.
Veröffentlicht: 12 November 2022
Gesehen am 20.03.2023